MAPPING OF FUELWOOD MARKETING POINTS AT KIYAWA TOWN, JIGAWA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Fuelwood is essential resource for the survival of most households in Nigeria because it provides energy to light, heat, and cook. This study was conducted to map out fuelwood marketing points in Kiyawa with a view to providing baseline information for future studies on woody species decline in the area. Garmin GPS (76cxs) was used to collect the coordinates of all fuelwood marketing points in the area while structured interview was used to identify the prevalent fuelwood species. ArcGis 10.2 was used to map out the marketing points while simple percentage was used to analyze the perceptions of the participants on the reason for choice of fuelwood species. This study found a total of 25 major fuelwood marketing points in the area. These serve as pools for stockfiling fuelwood sourced from the surrounding bushes and woodlands in northeastern Nigeria. A total of 16 species were identified at the marketing points out of which 14 are woody. The most prevalent wood fuel species located at the marketing points include Parkia biglobosa (10 locations), Azadirachta indica (7 locations) and Anogeissus leiocarpus (4 locations). The most preferred wood fuel species are Balanites aegyptiaca, Parkia biglobosa, Azadirachta indica and Piliostigma reticulatum. Reasons advance for choice of those species include its availability at the marketing points (50%), cost (28.57%) and wood quality (21.43). This study therefore recommended that policies and programmes should be mounted to combat over-exploitation of the prevalent plants in order to avoid the danger of extinction.
Keywords: : fuelwood, energy, bio-resources, woody species